A Radio Program: a Strategy to Develop Students’ Speaking and Citizenship Skills - María Fernanda Jaime Osorio; Mabel Catalina Caicedo Muñoz; Iván Camilo Trujillo Bohórquez (HOW)
This article reports on an action-research study which examined the impact of a radio program as a strategy to develop the speaking skills of a mixed course at a private institution in Colombia. Hence, data were collected from 18 students through tests, surveys, field notes, and interviews. The results indicate that there is an important relationship between the recording, broadcast, and reflection on a radio program and the development of students’ oral competence, their motivation for learning, the improvement of dialogue, and the coexistence of students.